Primary Current Test Method for Transformer Protection Based on Transient Load - Jiyin SHI (Zhongguo dianli)
When test load is insufficient, the current transformer (TA) secondary circuit test by primary current cannot be completed, which often results in the failure of new transformer protection to be put into normal operation. In order to solve this problem, a method for testing TA secondary circuit by using transient current such as motor starting current or transformer magnetizing inrush current is presented. The double-side current relationship of the transformer is analyzed with transient load flowing, and the current is reconstructed according to different wiring groups so that the currents on both sides are proportional. The signal correlation function is introduced to analyze and calculate the current waveform, and the phase angle difference and transformation ratio of TA on both sides of the transformer relative to the reference bay are obtained, thereby determining the correctness of TA secondary circuit. The engineering test results of the proposed method are consistent with that of traditional steady-state load test method, which proves its feasibility and correctness.